Marriage Conflicts Against the Psychology of Children - Pat Kurniati; Bunyamin Maftuh; Elly Malihah; Muhamad Subkhan; Sri Rumiati (UIN Sunan Gunung Djati Bandung, 2021)
The reality in society shows that not all married couples have the same relationship pattern. In the sense that the life forms they have to live are different from one another. There are married couples who after marriage have to live separately. On the other hand, husbands are also found in living their domestic lives in an effort to form a harmonious and happy family, always dealing with various conflicts that can affect the child's psychology. This research is a qualitative research with a descriptive approach through library research or library research that refers to sources of books, journals, and other references related to research.